Women's Transformative Leadership in Realizing the Vision of Education Sustainable - Mutmainnah; Afriani, Linda; Burhanuddin; Harimurti, Eka Rista (IJESS International Journal of Education and Social Science, 2025)
The transformative leadership of female principals plays a strategic role in addressing the challenges of 21st century education, especially in an effort to realize the vision of sustainable education. This research is motivated by the increasing participation of women in school leadership positions and the need for adaptive, inclusive, and visionary leadership. The purpose of this study was to identify the transformative leadership characteristics of female principals, analyze their leadership contributions in realizing the vision of sustainable education, and explore the challenges and adaptive strategies used. This study uses a literature review approach. This approach was chosen because it allows researchers to conduct critical synthesis of various scientific studies that have been published, both conceptually and empirically. The results showed that female school principals applied transformative leadership values such as ideal influence, inspirational motivation, intellectual stimulation, and individual attention. Female principals also play an active role in integrating the principles of Education for Sustainable Development (ESD) into managerial practices and developing adaptive strategies through strengthening social-professional networks, independent personal capacity development, and local context-based innovation.